2022
DOI: 10.1038/s41477-022-01222-x
|View full text |Cite
|
Sign up to set email alerts
|

The genome of homosporous maidenhair fern sheds light on the euphyllophyte evolution and defences

Abstract: Protein-coding gene annotation. To search for homologous genes, the protein sequences from all ferns and lycophytes transcriptomes in the OneKP project 1 were retrieved and aligned to the A. capillus-veneris genome, using GeneWise 2 . For transcriptome-based prediction, nineteen transcriptomes covering the entire life cycle of A. capillus-veneris were generated in this study (Supplementary Table 8). RNA was extracted using the Qiagen RNeasy protocol and sequenced on an Illumina HiSeq 4000 with a 300 bp insert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 121 publications
0
37
0
Order By: Relevance
“…" Wang and Bai (2019) have proposed a possible scenario regarding the transition from homospory to heterospory. Similar adaptive advantages of this transition might underlie the retention of the megasporangia in Fang et al, 2022), such LEC1-centered regulatory networks found in Adiantum capillus-veneris might have been available for integration with other evolutionary innovations, resulting in the origin of seeds, which would represent the kind of "tinkering" event suggested by Jacob (1977). Twenty years have passed since the original idea to explore the role of LEC1 in seed origin.…”
Section: Perspectivesmentioning
confidence: 90%
See 2 more Smart Citations
“…" Wang and Bai (2019) have proposed a possible scenario regarding the transition from homospory to heterospory. Similar adaptive advantages of this transition might underlie the retention of the megasporangia in Fang et al, 2022), such LEC1-centered regulatory networks found in Adiantum capillus-veneris might have been available for integration with other evolutionary innovations, resulting in the origin of seeds, which would represent the kind of "tinkering" event suggested by Jacob (1977). Twenty years have passed since the original idea to explore the role of LEC1 in seed origin.…”
Section: Perspectivesmentioning
confidence: 90%
“…A recently published work provides strong support for that hypothesis; based on the genome sequence and transcriptome analysis of Adiantum capillus-veneris , Fang et al (2022) determined that AcdLEC1 (previously designated as AcLEC1 ) is not only expressed during homosporangium development, but also resides at a hub of a regulatory network that is conserved in the Arabidopsis seed program. The work further elucidated the function of AcdLEC1 in pteridophytes, which consistent to the previous finding that the AcdLEC1 expressed in sporophytes under stress conditions ( Xie et al, 2008 ).…”
Section: Perspectivesmentioning
confidence: 96%
See 1 more Smart Citation
“…An extended gene family in Mango is the chalcone synthase ( CHS ) family, and certain genes within this family are likely to be involved in the biosynthesis of urushiols and related phenols ( Wang et al, 2020 ). The leaf and stem vascular regulator BRI1-BRL gene family was found to be expanded in Adiantum capillus-veneris L. and functionally conserved for vascular development regulation in euphyllophytes, suggesting that complicated vascular system formation led to the origin of true leaves or euphylls ( Fang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…10,000 species, the H. ensiformis mitogenome again adds to the list of astonishing molecular peculiarities that are hallmarks of vascular plant mtDNAs 44,45 . Given its extraordinary complexity, it comes as no surprise that no other leptosporangiate mitogenome has previously been assembled despite multiple NGS efforts including the water fern genera Azolla and Salvinia 46,47 or the "flying spider-monkey" tree fern Alsophila spinulosa 48 or, most recently, the model ferns Adiantum capillus-veneris 49 and Ceratopteris richardii 50 . Likewise no mitogenome was reported in a genome assembly effort for the lycophyte Isoetes taiwanensis 51 , possibly owing to even higher complexity than the ones reported previously for Isoetes engelmannii and Selaginella moellendorffii 7,8 .…”
Section: A First Leptosporangiate Fern Mitogenome Assemblymentioning
confidence: 99%